2017
DOI: 10.1177/0894439317744163
|View full text |Cite
|
Sign up to set email alerts
|

Government Formation and Political Discussions in Twitter: An Extended Model for Quantifying Political Distances in Multiparty Democracies

Abstract: The Retweet Overlap Network (RON) method has proved to be successful in quantifying the distances between political parties in multiparty democracies (Guerrero-Solé, Corominas-Murtra & López-González, 2014; Guerrero-Solé, 2017). These distances are frequently used in political science to explain the formation of coalitions and governments (Volden & Carrubba, 2004). This paper aims to explore how the data collected from Twitter can be related to the ideological similarities between political parties drawing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 83 publications
0
13
0
2
Order By: Relevance
“…A final complementary approach to users’ interactive behavior was done by building the RONs. RON is a method that has been proven efficient to estimate political homophily and polarization in Twitter (Guerrero-Solé, 2017; Guerrero-Solé & López-González, 2017). RON draws on the measurement of the overlaps between the communities of retweeters of the most influential (retweeted) users in a network.…”
Section: Sample and Methodsmentioning
confidence: 99%
“…A final complementary approach to users’ interactive behavior was done by building the RONs. RON is a method that has been proven efficient to estimate political homophily and polarization in Twitter (Guerrero-Solé, 2017; Guerrero-Solé & López-González, 2017). RON draws on the measurement of the overlaps between the communities of retweeters of the most influential (retweeted) users in a network.…”
Section: Sample and Methodsmentioning
confidence: 99%
“…On the one hand, when looking at news consumption, several articles showed that social media and search engines diversify people's news diets [64,[139][140][141][142]. On the other hand, when considering social networks and the impact of digital media on homophilic structures, the literature contains consistent reports of ideologically homogeneous social clusters [143][144][145][146][147]. This underscores an important point: Some seemingly paradoxical results can potentially be resolved by looking more closely at context and specific outcome measurement.…”
Section: Few Articles Have Shed Light On Causal Effects Between Social Media Use and Trust A Field Experiments In The Unitedmentioning
confidence: 99%
“…Para responder a la segunda pregunta de investigación, sobre las distancias ideológicas entre partidos en las elecciones de abril y noviembre de 2019 y las diferencias observadas entre estas distancias y las de las elecciones de 2015 y 2016, calculamos los valores de las intersecciones entre los principales partidos, agrupando las comunidades de retuiteadores de los miembros de cada partido. Esto permite aproximarse mejor a la distancia entre partidos, si asumimos que las intersecciones entre comunidades pueden ser un buen indicador de estas distancias (Guerrero-Solé & López-González, 2019). En las tablas 2 y 3 se muestran las intersecciones entre las comunidades de retuiteadores de los partidos para las elecciones del 28 de abril y de 10 de noviembre de 2019, respectivamente.…”
Section: Resultsunclassified
“…Esta técnica es análoga a la de cocitación, y permite descubrir la estructura de comunidades, así como de algunos de los atributos latentes de los usuarios que participan en la discusión (Guerrero-Solé, 2018). Además de ser un método eficaz para la identificación de comunidades, también ha sido utilizado para calcular las distancias entre partidos políticos que se han relacionado con la distancia ideológica y con las preferencias de los votantes para formar pactos después de las elecciones (Guerrero-Solé et al, 2014;Guerrero-Solé, 2018;Guerrero-Solé & López-González, 2019). Para una explicación en detalle del método, que utiliza el coeficiente de Jaccard para el cálculo de distancias, veáse Guerrero-Solé y López-González (2019).…”
Section: Método Y Muestraunclassified